Efecto de la aplicación de anabólicos vegetales y sintéticos en la etapa de crecimiento y finalización en cerdos - Ledesma Padilla, Karla Naomi (2023)
Pig farming is one of the lines of production within the agricultural sector that generates dynamism within the country's economy, because it is responsible for generating income, sources of employment and income for people engaged in raising pigs. In this sense, due to the fact that 70% of the pig raising expenses are destined to their feeding, it is necessary to develop strategies and procedures that optimize the growth and fattening of the pigs in order to increase the profit margins and deliver to the market a quality product that meets the standards required by the swine sector. In this sense, the present research is focused on analyzing the impact on weight gain and growth in Large White breed pigs, by means of two anabolics spread in the market, a synthetic Boldenone and a vegetable Zeramec, with the purpose of testing their performance, nine experimental subjects with similar conditions in reference to age and weight were used, in addition, Vitamin AD3E was applied to the subjects. To analyze the difference of means, the statistical technique of completely Randomized Design DCA and ANOVA of one factor was used. The results obtained show that the synthetic anabolic Boldenone proves to be the treatment that generates the best margins of weight gain and growth in the experimental subjects, under a 95% of significance a p-value of <0.0001 is obtained in weight gain and a p-value of 0.0001 in growth, which provides statistical evidence that the best treatment is based on Boldenone. From the same, the results of feed conversion denote that T1 based on Boldenone is the one with the best feed conversion with a value of 3.18, followed by T2 with a value of 3.36 and finally T0 with a value of 3.41. Finally, the profit margin presents different results in each treatment, since the treatment based on Boldenone presents 341.89 dollars, the treatment based on Zeramec 153.83 and the control treatment 137.19 dollars of profit.